Comparative analysis of weed management techniques in taro (Colocasia esculenta (L.) Schott) - Paul, S; Rahman, M H; Tamanna, M; Halder, D; Kobir, M S; Munshi, M H; Hajong, P; Anwar, M B (Plant Science Today, 2025)
Weed management poses a significant challenge in taro cultivation since it’s a long-duration crop grown during the monsoon season. The warm, humid conditions of its extended growing period promote rapid weed germination and growth, complicating weed management efforts. To address this issue, a study was conducted at the Bangladesh Agricultural Research Institute, Jashore, in 2021 and 2022 to evaluate sustainable weed management strategies for taro. The experiment, designed as a randomized complete block (RCB) with three replications, tested seven weed control methods: T1= straw mulching (SM), T2= pre-emergence herbicide+SM, T3= poly mulching (PM), T4= pre-emergence herbicide+PM, T5= intercropping+two hand-weeding, T6= pre-emergence herbicide, and T7= four hand-weeding, alongside T8= weed-free and T9= weedy control treatments. Results indicated that all mulching treatments achieved 70% to 80% weed control efficiency, significantly reducing weed growth up to 120 days after emergence (DAE). The intercropping+hand-weeding treatment provided 75% to 80% weed control up to 90 DAE. Among the mulches, straw mulching resulted in the tallest and widest plant base girths, leading to the highest yield and benefit-cost ratio, followed by other mulch and intercropping+hand-weeding treatments. Pre-emergence herbicide treatments were ineffective due to their short duration of action. Additionally, combining mulching (SM & PM) with pre-emergence herbicide offered no advantage over mulching alone. These findings highlight straw mulch as the most effective weed management strategy for taro, eliminating the need for herbicides. Where mulch is unavailable, intercropping combined with hand weeding can be a viable alternative for effective weed control.